New effective moduli of isotropic viscoelastic composites. Part II. Comparison of approximate calculation with the analytical solution; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Kupriyanov N. A. Nikolay Amvrosievich (Numerical Simulation of Applied Problems, 2016)
Title screen